Yellow Fly, Diachlorus ferrugatus (Fabricius) (Insecta: Diptera: Tabanidae) - G. B. Fairchild; Howard V. Weems, Jr.; Thomas R. Fasulo (EDIS)
In Florida, the name "yellow fly" is commonly used to describe a group of about a dozen different yellow-bodied biting flies in the Tabanidae family. However, Florida tabanid experts recognize only one species, Diachlorus ferrugatus (Fabricius), as the "true" yellow fly. (Cilek 2000a). In Belize this species is known as the "doctor fly." The yellow fly is a fierce biter. Like mosquitoes, it is the female fly that is responsible for inflicting a bite. The males are mainly pollen and nectar feeders. Tabanids are most likely encountered in hot summer and early fall weather. They are active during daylight hours. This document is EENY-320 (originally published as DPI Entomology Circular 139), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: April 2004.